2022
DOI: 10.1002/slct.202103521
|View full text |Cite
|
Sign up to set email alerts
|

Selective Photocatalytic Conversion of Benzyl Alcohol to Benzaldehyde by Antimony(V) Porphyrin Metal‐Organic Frameworks under Visible‐Light Irradiation

Abstract: Porphyrin‐based MOFs have great structural tunability and prominent catalyst activity. In this work, a series of antimony porphyrin MOFs (PCN‐224(Sb)‐L) were synthesized to efficiently selective oxidate benzyl alcohol under visible light. To investigate the effects of the Sb‐axial ligands on photocatalytic activity, the oxidation of benzyl alcohol to corresponding benzaldehyde was utilized as a model reaction. Within these three analogues of PCN‐224(Sb)‐L, PCN‐224(Sb)‐OH exhibit a remarkable 96 % conversation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…[19] The role of antimony-porphyrin complexes in photocatalytic organic transformation reactions is scarcely reported in the literature. [20][21][22] However, such reports on antimony-corrole complexes are very few. [4g-h, [23][24][25][26][27][28][29][30] Corrole, a contracted version of porphyrin having an 18π electron aromatic system has attracted considerable research interest in recent times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] The role of antimony-porphyrin complexes in photocatalytic organic transformation reactions is scarcely reported in the literature. [20][21][22] However, such reports on antimony-corrole complexes are very few. [4g-h, [23][24][25][26][27][28][29][30] Corrole, a contracted version of porphyrin having an 18π electron aromatic system has attracted considerable research interest in recent times.…”
Section: Introductionmentioning
confidence: 99%
“…The radical cation of antimony porphyrin behaves as a potent oxidant and can oxidize a host of chemicals like phosphine, alkene, and water [19] . The role of antimony‐porphyrin complexes in photocatalytic organic transformation reactions is scarcely reported in the literature [20–22] . However, such reports on antimony‐corrole complexes are very few [4g–h,23–30] .…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] The preparation of bimetallic active site MOFs has proven to be excellent approach to improve catalytic performance. [19][20][21] For example, Feng et al [22] reported a photocatalytic strategy to achieve the reduction of nitroarenes to anilines catalyzed by In/Pd bimetallic MOFs. The photocatalytic activity of the resultant In/Pd MOFs was attributable to the synergistic effect of In and Pd ions, which enhanced electron-hole separation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…However, single‐metal Porphyrin‐MOFs are difficult to meet the requirements of multifunctional catalysis owing to its own nature [15–18] . The preparation of bi‐metallic active site MOFs has proven to be excellent approach to improve catalytic performance [19–21] . For example, Feng et al [22] reported a photocatalytic strategy to achieve the reduction of nitroarenes to anilines catalyzed by In/Pd bimetallic MOFs.…”
Section: Introductionmentioning
confidence: 99%